Salivary Duct Carcinoma: Case Reports and Brief Review of the Literature - Deepti Kantamani; Sai S. Bandaru; Jennifer L. Miatech; M. Patrick Stagg (Case Reports in Oncological Medicine)
Salivary duct carcinoma (SDC) is an uncommon and highly aggressive tumor associated with high morbidity and mortality. According to the World Health Organization, it is an extremely rare malignancy with an estimated incidence of 1-1.2 in 1,000,000 patients. Standard treatment for SDC is wide surgical resection along with lymph node dissection followed by adjuvant radiation therapy. The role of adjuvant chemotherapy is not known. In this report, we present three cases of SDC. A 71-year-old female with T1N0M0 disease was treated with total parotidectomy, ipsilateral neck dissection, and adjuvant radiotherapy without evidence of disease recurrence at 5 months. The second is a 59-year-old female with TXN1M0 disease who was treated with total parotidectomy with ipsilateral level I-IV neck dissection and adjuvant radiotherapy without evidence of disease occurrence at 21 months. The third case is a 79-year-old male with widely metastatic disease, including brain metastases, treated with cranial irradiation, leuprolide, and lapatinib who remains under home hospice care.